Self-Regulated Learning of Arabic Education Students via Moodle Discussion Forum - Saproni Muhammad Samin; Hikmah Hikmah (Jurnal Alsinatuna, 2021)
This study aims to analyze and describe the Self-Regulated Learning of Arabic Language Education students at the Universitas Islam Riau. The research method used is a descriptive analysis using the percentage of the Self-Regulated Learning questionnaires through the Moodle discussion forum, which consists of five aspects, that is discipline, confidence, motivation, initiative, responsibility, with a sample of forty-four students. The validity test results using the SPSS 20. There are eight invalid and seventeen valid questions from the twenty-five indicator items after the validity test, so the researchers only used the right questions to test the research object. Based on the Cronbach's Alpha value in the reliability statistics table, a matter of 0.840, this can conclude that these results have a very high level of reliability. The study results indicate that the Self-Regulated Learning of Arabic Language Education students at the Universitas Islam Riau is pretty good in the aspects of self-confidence with a score of 65.7%, aspects of discipline with a score of 72.2%, and aspects of responsibility with a score of 73.1%, And not good in the part of the initiative with a score of 55.1% and motivational elements with 63.8%.